2015
DOI: 10.1159/000438515
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Improves Porcine Parthenogenetic Embryo Development Through Transient Remodeling of Histone Modifiers

Abstract: Background/Aims: Parthenogenetic embryos are useful in many applications, such as being an alternative source of embryonic stem cells that would avoid ethical problems. Aberrance in epigenetic reprogramming is considered the major reason for the developmental failure of parthenogenetic embryos. Many histone deacetylase inhibitors have been shown to improve the reprogramming of stem cells and embryos. Here, the relationship between histone modification and parthenogenetic embryonic development was explored. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…We observed absence or weak fluorescent intensity for H3K27me2 in zygotes, which differs from previous studies in mice reporting intensive H3K27me2 signal in PNs of mice zygotes (Erhardt et al, 2003). Conversely, we observed a prominent fluorescent signal for H3K27me2 in D6 and D8 IVF blastocysts, while another study reported that H3K27me2 levels were nearly undetectable in porcine blastocysts produced by parthenogenetic activation (Huang et al, 2015). Differences between fertilized and parthenogenetic embryos have been reported regarding other histone modifications including H3K9ac and H3K27ac (Huang et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…We observed absence or weak fluorescent intensity for H3K27me2 in zygotes, which differs from previous studies in mice reporting intensive H3K27me2 signal in PNs of mice zygotes (Erhardt et al, 2003). Conversely, we observed a prominent fluorescent signal for H3K27me2 in D6 and D8 IVF blastocysts, while another study reported that H3K27me2 levels were nearly undetectable in porcine blastocysts produced by parthenogenetic activation (Huang et al, 2015). Differences between fertilized and parthenogenetic embryos have been reported regarding other histone modifications including H3K9ac and H3K27ac (Huang et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…HDAC inhibitors are being increasingly used in IVC treatment for improving the efficiency of SCNT and parthenogenetic activation [42]. In this study, we sought to improve the development of porcine SCNT embryos with LAQ824 (class I, IIa and IIb HDAC inhibitor) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We found that VPA induces increased levels of H3K4me2/me3 and H3K9me markers, which are associated with active gene transcription and have been previously reported after treatment with HDAC inhibitors, including VPA, in HL60 cells, mouse embryonic stem cells, primary blast cells of patients with acute myeloid leukemia, rat astrocytes and cortical neurons, fibroblasts, human breast cancer cells, pig embryos, rat hippocampus and a human leukemia cell line [20,[48][49][50][67][68][69][70][71]. The abundance of H3K4me2/me3 in the presence of VPA in HeLa cells was associated with increased gene expression of the methyltransferase KMT2D.…”
Section: Discussionsupporting
confidence: 75%